Pengaruh Atribut Komite Audit Terhadap Manajemen Laba - Verasella Christine, (2021)
This study aims to determine the effect of the attributes of the audit committee on earnings management. Cohen's model is used to measure real earnings management. The sample used is 131 manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. This research is a type of quantitative research using secondary data in the form of annual reports and company financial report. Fixed Effect Model (FEM) with panel data regression used in this study using STATA version 16. Based on the results of the test and analysis, it can be said that audit committee size has an effect significant and negative on earnings management and the control variables, namely firm size and profitability have a significant negative effect on earnings management. Meanwhile, the tenure, expertise and overlapping of the audit committe have no effect on earnings management and the control variable, namely leverage has no effect on earnings management. The results of this study have an influence for potential investors and regulators to develop the influence of the attributes of the audit committee on earnings management.